2011
DOI: 10.1093/glycob/cwr150
|View full text |Cite
|
Sign up to set email alerts
|

The WaaL O-antigen lipopolysaccharide ligase has features in common with metal ion-independent inverting glycosyltransferases*

Abstract: WaaL is a membrane enzyme that catalyzes a key step in lipopolysaccharide (LPS) synthesis: the glycosidic bonding of a sugar at the proximal end of the undecaprenyl-diphosphate (Und-PP) O-antigen with a terminal sugar of the lipid A-core oligosaccharide (OS). Utilizing an in vitro assay, we demonstrate here that ligation with purified Escherichia coli WaaL occurs without adenosine-5'-triphosphate (ATP) and magnesium ions. Furthermore, E. coli and Pseudomonas aeruginosa WaaL proteins cannot catalyze ATP hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 67 publications
3
74
0
Order By: Relevance
“…This result is in agreement with data obtained by Ruan et al (48) for the O antigen ligase WaaL from E. coli, which is homologous to PglL and catalyzes the glycan transfer from the undecaprenylpyrophosphate lipid carrier to lipid A. These authors showed that WaaL does not require a divalent metal cation for its activity (48).…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with data obtained by Ruan et al (48) for the O antigen ligase WaaL from E. coli, which is homologous to PglL and catalyzes the glycan transfer from the undecaprenylpyrophosphate lipid carrier to lipid A. These authors showed that WaaL does not require a divalent metal cation for its activity (48).…”
Section: Discussionsupporting
confidence: 93%
“…The WaaL enzyme that ligates nascent O-antigens to lipid A is specific for Und-PP-linked glycan donors, and its mechanism and architecture are conserved across species (58). This enzyme is unaffected by the pathway of O-antigen biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments of this work were carried out on a WaaL construct with a C-terminal FLAG-His10x tag, containing 32 additional residues, and resulting in an overall average MW of 50794.8 Da. The protein was purified from E. coli JM105v by Ni 2+ -affinity chromatography, and it was subsequently concentrated using a 30 kDa cutoff membrane as described [59]. This method afforded~1 mg of WaaL protein per liter of culture.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…The experiments of this study were conducted on DM-solubilized protein. Enzyme activity was verified by an in vitro ligation assay [59]. Buffer exchange yielded stock solutions containing 100 μM WaaL, 0.05% (wt/vol) DM, 150 mM sodium chloride, 12.5 mM imidazole, 10% glycerol, and 50 mM sodium phosphate (pH 8).…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation